Using Percentile Schedules to Increase Academic Fluency. (25th February 2016) - Clark, Alison M.; Schmidt, Jonathan D.; Mezhoudi, Nabil; Kahng, SungWoo
Abstract : After a learner becomes accurate with a task, fluency must be shaped over time to reach the target goal. However, shaping criteria can be somewhat arbitrary; thus, an objective criteria has the potential to improve implementation consistency. One such method is through the use of percentile schedules. The purpose of the current study was to use a percentile schedule as a means of determining the reinforcement criterion to improve the fluency for three academic tasks. The participant was a 14‐year‐old boy diagnosed with developmental disabilities. The use of the percentile schedule based reinforcement criterion resulted in increased fluency with two of the three academic tasks. This study suggests that percentile schedules may provide an objective criterion for improving fluency. Copyright © 2016 John Wiley & Sons, Ltd.